HUMAN RESOURSES IN MODERN TRADE COMPANIES - Dukoski, Sasha; Veljanovska, Svetlana; Dukoska, Marija (Horizons - International Scientific Journal, 2021)
In the contemporary and highly dynamic surrounding conditions, now, business more than ever depends on: attracting, detaining and effectively taking advantage of, basically, chronically scarce resource - highly professional and skilled staff. In addition, competitive ability on human resources in contemporary trade associations, because of the entire business climate, is quite dynamic and constantly exposed by many factors. The most complex, at the same time, of the most essential importance are: The constant changes of the legislation in the area of ​​the organization in the trade associations, the conditions of the defined market, the intense competition, as well as the fastidiousness and emerging requirements from the clients, in other words the consumers. All this has its own particular influence on the professional parameters for work, thereby making an additional pressure on the constantly disposable resources. Human resources in one trade association include all the employees, irrespective of their position, education or their level of commitment. Basically, contemporary conditions of management are protecting the human as a crucial resource for the company, in which he largely determines the competitive ability of it. On the account of preserving, and above of all, the development on the competition ability on one trade association in a defined business area is in a direct interaction of instruction: new standards, skills, knowledge and ethics in business. All of this is a precondition for survival and satisfying needs, as long as there is a wish to achieve success in more intense conditions for work and survive on the only relevant place where all that is valued - the market.